The Relationship Between Production Inputs, Factor Substitution, and Economic Growth - Yıldırım, Abdulmecit (My University, 2022)
Factors of production and elasticity of substitution play an essential role in economic growth accounting. Although production functions with constant elasticity of substitution between factors are more commonly utilized in growth accounting, studies based on production functions with variable elasticity of substitution are also conducted. Since production functions with variable elasticity of substitution provide more flexibility in parameters, they are more advantageous than other production functions. Besides, most studies focus on the elasticity of substitution between capital and labor. Studies on the sub-components of production factors are relatively few. In this study, capital stock is analyzed by dividing it into two subcomponents as public capital stock and private capital stock. The empirical results, in general, show that the elasticity of substitution between the public capital stock and the private capital stock is less than unity. In this context, public and private capital stock can be expressed as complementary inputs in the final production of goods and services. As a result, public expenditures on infrastructure can boost economic growth by raising the efficiency of private investments.
Keywords: Public Capital; Private Capital; Production Function; Economic Growth; The elasticity of Substitution